Analisis Faktor Penerimaan Media Sosial Pemerintah (Studi Kasus Instagram Dinas Pariwisata Kota Palembang @charming.palembang) - Aulia Syahrani; Dwi Rosa Indah (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
In today's rapidly growing internet era, humans are required to be able to adapt to change, like how to communicate. Courageous communication can be done through social media such as Instagram, Whatsapp, Facebook, etc. Instagram itself is not only used by individuals but by agencies/companies as well. One agency that uses Instagram social media is the Palembang City Tourism Office. Instagram is used as a forum for communicating and sharing information about tourism promotions in the city of Palembang. Currently the Palembang City Tourism Office's Instagram account @charming.palembang is still not proven effective due to the lack of two-way communication and responses from readers (likes, comments, shares, etc.). Therefore, it is necessary to measure social media acceptance using the UTAUT model with a sample of 126 people who are followers of the Instagram account @charming.palembang. Then, the data is processed using the SmartPLS application. Results showed that PE and SI had a significant relationship with BI but EE did not. Meanwhile, BI has a significant relationship with UB but FC did not. For the moderating variables, gender, age, and experience alone do not moderate the relationship between the existing independent and dependent variables.